Las nuevas tecnologías al servicio de las democracias - Melgoza López, Cristina (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
The rapid technological advances in the 21st century have transformed our societies, and therefore, our democracies are undergoing constant changes to adapt to the impacts of these new technological contexts. This thesis analyzes electronic voting via the Internet, examining its technological foundations, advantages, and challenges. Both the technical and security aspects, as well as the political and social implications of electronic voting, are reviewed, adopting a multidimensional perspective, and the use of electronic voting over the Internet is proposed as an instrument to facilitate voting for different groups, such as people with disabilities. Mexicans abroad, at the same time, seek to encourage the participation of young people in the electoral process.

Los rápidos avances tecnológicos en el siglo XXI han transformado nuestras sociedades y, por ende, nuestras democracias están sufriendo cambios constantes para adaptar a los impactos de estos nuevos contextos tecnológicos. En la presente tesis, se analiza el voto electrónico vía internet, examinando sus fundamentos tecnológicos, ventajas y desafíos. Se revisan tanto los aspectos técnicos y de seguridad, como las implicaciones políticas y sociales del voto electrónico, adoptando una perspectiva multidimensional y, se propone el uso del voto electrónico por internet como instrumento para facilitar la votación de diferentes grupos tales como: personas con discapacidad, mexicanos en el extranjero, al mismo tiempo se busca fomentar la participación de los jóvenes en el proceso electoral.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2024-0304; Ciencias políticas; Democracia; Era digital; Voto electrónico; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18613